QUALITY ISSUES IN NEWS COVERAGE OF DILMA ROUSSEFF’S IMPEACHMENT: an analysis of six Brazilian newspapers - Santos, Ebida; Guazina, Liziane Soares (Brazilian journalism research, 2020)
This article aims to discuss quality issues in political journalism from six Brazilian newspapers and their coverage of Dilma Rousseff’s impeachment process in 2016. We analyzed three major national newspapers (Folha de S. Paulo, O Globo, and Estado de S. Paulo) and three regional newspapers (A Tarde, O Liberal and Zero Hora). To do this we applied the methodology adapted from the Journalistic Added Value (VAP) together with quantitative and qualitative analyses. The study reveals the main quality issues in news coverage to be: the influence sources had on selecting which issues would be reported on; the lack of thematic diversity; the officialism of the sources; and the lack of time constraints on post-impeachment. O presente artigo tem como objetivo discutir problemas de qualidade verificados no jornalismo político praticado por seis jornais brasileiros durante a cobertura do processo de impeachment de Dilma Rousseff em 2016. Foram analisados três jornais nacionais de referência: Folha de S. Paulo; O Globo; e Estado de S. Paulo e três jornais regionais: A Tarde; O Liberal e Zero Hora. Para tanto, utilizamos a metodologia adaptada do Valor Agregado Periodístico – VAP, em um cruzamento de análises quantitativas e qualitativas. O estudo demonstra que os principais problemas de qualidade na cobertura ocorreram em aspectos relativos à influência das fontes na seleção do que é noticiado; à falta de diversidade temática; ao oficialismo das fontes; e à ausência de consequências temporais sobre o pós-impeachment. El artículo tiene como objetivo discutir problemas de calidad en el periodismo político practicado por seis periódicos brasileños durante la cobertura del proceso de destitución de Dilma Rousseff en 2016. Se analizaron tres periódicos nacionales de referencia: Folha de S. Paulo; O Globo; y Estado de S. Paulo y tres periódicos regionales: A Tarde; O Liberal y Zero Hora. Para eso, utilizamos la metodología adaptada del Valor agregado periódico – VAP, en un cruce entre análisis cuantitativo y cualitativo. El estudio muestra que los principales problemas de calidad en la cobertura ocurrieron en aspectos relacionados con la influencia de las fuentes en la selección de lo que se informa; la falta de diversidad temática; el oficialismo de las fuentes; y la ausencia de consecuencias temporales en el post-juicio político.